The Concepts of Persistent and Permanent in Non Semi-Simple DNA Splicing System - Yuhani, Yusof; Nor Haniza, Sarmin; Fong, Wan Heng (2014)
The investigation on the behavior of deoxyribonucleic acid (DNA) splicing languages has been of interest of many biologists and mathematicians. Yusof-Goode (Y-G) splicing system has been introduced for the purpose of showing the transparent biological process of DNA splicing systems. In this paper, the approach of Y-G splicing system is applied in presenting the persistency and permanent characteristics of non semi-simple DNA splicing system of Type I and Type II.